The whole is larger than the sum of its parts: additive effects of SMS nudge bundles - Barbosa, Sergio; Bermúdez, Juan Pablo (Frontiers in Communication, 2024)
Public access to housing is a challenge for a large number of societies and follows a great number of limitations. Here, we test several SMS-interventions aiming at motivating people to get information on affordable loans for housing options actually available to them. We randomly assigned 6247 people to receive an SMS inviting them to get information about government backed housing loans for which they were already eligible. SMSs followed one of 14 possible nudges including “simple” nudges (e.g. messages personalised with the recipient's name or mentioning a social norm) andor “bundled” nudges (combining personalization with another simple nudge). We observed SMS response rates (i.e. responding to sign up for receiving more information) according to which nudge was assigned. No other independent variable was considered. While most nudges were more effective than a control SMS, we observed significant variation across nudges on their ability to elicit responses from users. Combinations of multiple nudges were more successful in responsebehaviour elicitation than simple nudges. We discuss the possible implications of “single” or “bundled” SMS on response rates and as an effective tool of behaviour change.